Fertility preservation in Turner syndrome: Karyotype does not predict ovarian response to stimulation. (15th September 2019) - Vergier, Julia; Bottin, Pauline; Saias, Jacqueline; Reynaud, Rachel; Guillemain, Catherine; Courbiere, Blandine
Abstract: Objective: Turner syndrome (TS) is responsible for gonadal dysgenesis with high risk of premature ovarian insufficiency. Little is known about fertility preservation (FP) strategies is this population. Design: Data from women with TS consulting with a fertility specialist in our FP centre from 2014 to 2018 were retrospectively collected. Measurement: Total number of mature oocytes cryopreserved using vitrification. Patients: Nine women with TS were referred. Three women with different karyotypes underwent controlled ovarian stimulation (COS) for oocyte vitrification. Mean age at TS diagnosis was 13.7 years [9‐20]. Mean referral delay between TS diagnosis and fertility consultation was 9.7 years [7‐14]. First counselling for FP was provided at 23.7 years [18‐28]. Mean AMH serum level prior to COS was 53.8 pmol/L [3.6‐95]. Results: All three women succeeded in obtaining cryopreserved oocytes with a mean number of 15.3 per woman [9‐20] and 9.2 per COS cycle [2‐20]. Ovarian response to COS was unexpectedly remarkable for the woman with a complete 45, X monosomy. Procedure was well tolerated for all women. None of them have used oocytes for in vitro fertilization yet. Conclusions: Independently of karyotype, antral follicular count, AMH and FSH levels seemed to be reliable predictive markers of oocyte cryopreservation success. In a monosomic TS woman, cryptic ovarian mosaicism could explain a successful ovarian response to stimulation with a high number of retrieved oocytes. In case of spontaneous menarche, TS adolescents should be referred during transition to adulthood for FP counselling to avoid referral delay and limit time‐related diminished ovarian reserve.